Structural style of mineral deposits in the Huamachuco-Cajabamba strip: North Peruvian Andes - Jacay, Jacay (2003)
The North Peruvian Andes present a remarkable and complete cretaceous sedimentation accumulated in a siliciclastic and carbonate platform, with a very important subsidence; which, during the Cenozoic, was affected by a compressive tectonic style, which generated a system of folds and reverse faults with vergence to the east. This entire system is cut by numerous stocks and porphyritic subvolcanic domes of acid composition, which follow an Andean course (approximately NW-SE), which have served as a source of mineralizing fluids for the different mineralized areas in the strip between the sierra of the department of La Libertad and the south of the department of Cajamarca (7 ° -8 ° S). Within this strip, various prospects of epithermal mineralization of precious minerals (Au) are associated with compressive shear zones, which have siliciclastic sequences from the Chimú Formation (Lower Cretaceous) as their host rock, which have been tectonized towards the end. from the Middle Eocene and mineralized during the Miocene. Some structural elements (such as transpressive faults, folds, etc.) that have controlled the entrapment of mineralization are exposed in the present work.